THE FUND OF LAND AS A SOURCE FOR INCREASING THE INCOME OF THE SPECIAL FUND OF THE MINISTRY OF DEFENSE OF UKRAINE - Сизов, А.; Кузьменко, В. (Київський національний університет імені Тараса Шевченка, 2020)
The article analyses the state and development of the fund of land of the Ministry of Defense of Ukraine in the course of the years of Ukrainian independence in accordance with the data presented by the State geographical cadstre and the Ministry of Defense of Ukraine, particularly: the peculiarities of their extortion and return as a result of court investigations. The main issues of the circulation of land are presented, as well as the mechanism of its introduction and the fact that it is economically appropriate, together with ways for solving the issues mentioned. The order for assessing the value of land property has been determined and proven by arguments, both the necessity and effective methods of further using the lands of the Ministry with a perspective of increasing the possible income to the special fund of the Ministry of Defense of Ukraine by selling or leasing them. The most attractive method to increase the income of the special fund of the Ministry of Defense has been chosen due to the circulation of land used mentioned for defense purposes. The legal subjects to use the land, presented for defense purposes are military units, facilities, military-educational institutions, enterprises and organizations of the Armed Forces of Ukraine, other military formations, that are functioning as independent judicial entities. Pieces of land property to the mentioned subjects are usually given for permanent use. Regardless of the tasks and functions, the users of the land for defense purposes are responsible for, they enjoy and are entitled to overall rights granted to all the land users, and do also perform the appropriate duties concerning the assurance of rational using and the appropriate defense of land resources.

У статті проаналізовано стан та розвиток банку земель Міністерства оборони України за роки української незалежності згідно з даними Держгеокадастру та Міністерства Оборони України, а саме: особливості їх відчуження та повернення за результатами судових розслідувань. Наведено основні проблеми земельного обігу, економічну доцільність та механізм його запровадження, а також шляхи вирішення проблем. Визначено та обґрунтовано порядок оцінки вартості земельних ділянок, необхідність та ефективні методи подальшого використання земель міністерством з прогнозом збільшення можливих надходжень до спеціального фонду Міністерства оборони України за рахунок продажу земель або надання їх в оренду. Обрано найбільш привабливий метод збільшення доходів спеціального фонду Міністерства оборони України за рахунок обігу земель оборони. Суб'єктами права користування землями, наданими для потреб оборони, виступають військові частини, установи, військово-навчальні заклади, підприємства та організації Збройних Сил України, інші військові формування, які функціонують як самостійні юридичні особи. Земельні ділянки цим суб'єктам надаються головним чином у постійне користування. Незалежно від завдань і функцій, покладених на користувачів землями оборони, вони користуються загальними для всіх землекористувачів правами, а також виконують відповідні обов'язки, пов'язані із забезпеченням раціонального використання та належної охорони земельних ресурсів.
БАНК ЗЕМЕЛЬ ЯК ДЖЕРЕЛО ЗБІЛЬШЕННЯ ДОХОДІВ СПЕЦІАЛЬНОГО ФОНДУ МІНІСТЕРСТВА ОБОРОНИ УКРАЇНИ
Keywords: fund of land; circulation of land; land property; land for defense purposes; банк землі; обіг землі; земельна ділянка; землі оборони